Combatting Pseudomonas aeruginosa with β-Lactam Antibiotics: A Revived Weapon? - Dylan W. Zhao; Christopher T. Lohans (Antibiotics)
Pseudomonas aeruginosa is a significant threat to public health as an aggressive, opportunistic pathogen. The use of β-lactam antibiotics such as penicillins, cephalosporins, monobactams, and carbapenems remains a front-line treatment against P. aeruginosa. However, the widespread use of β-lactams has led to the emergence of β-lactam-resistant isolates that significantly increase the economic burden and risk of mortality in patients. With the declining productivity of the antibiotic discovery pipeline, research has investigated synergistic agents to revive the use of β-lactam antibiotics against β-lactam-resistant P. aeruginosa. In this review, we summarize the mechanism of β-lactam antibiotics and provide an overview of major mechanisms associated with β-lactam resistance in P. aeruginosa. We then describe the background and use of three promising classes of agents that have shown extensive beneficial effects with β-lactam antibiotics against P. aeruginosa, namely β-lactamase inhibitors, bacteriophages, and antimicrobial peptides. The current understanding of the mechanisms of these synergistic agents is discussed. Lastly, we provide an overview of the current barriers impeding antibiotic development, and offer a glimpse into recent advances of artificial intelligence-based discovery that may serve as a new foundation for antimicrobial discovery and treatment.